A long way from tax justice: the Brazilian case - Lena Lavinas; Thiago Andrade Moellmann Ferro (International Labour Organization (ILO), 2014)
This paper presents the major characteristics of the Brazilian tax system, after underlining the modifications it went through since 1988, when the country adopted a new and democratic Constitution. One important feature is the marked incidence of indirect consumer and production taxes (49% of all tax revenues) in place of direct taxes on income, inheritance, and capital gains. This imbalance between indirect and direct taxes explains, in large part, the elevated regressivity of the Brazilian tax system, which both expresses and reproduces the profound inequalities that characterize Brazilian society.
Keywords: 330; tax system; taxation; tax policy; trend; Brazil